Failure of steam line causes determined by NDT testing in power and heating plants - Srdjan Bulatovic; Vujadin Aleksic; Ljubica Milovic (Fracture and Structural Integrity)
This paper examines leakage and damages of steam and provides an overview of NDT testing in order to determine the cause of steam lines failure in power plants and heating plants. This approach may be applied to similar structures and its application in preventive maintenance would help extend the life of steam pipes.